Youth blogging and serious illness. Issue 1 (15th December 2015) - Nesby, Linda; Salamonsen, Anita
Abstract : In recent years, a growing number of young people who experience illness tend to blog about it. In this paper, we question whether and how illness blogs illustrate the intercommunicative aspect of blogging by bringing forth both the literary concept of the implied reader and the sociological concepts of empowerment and agency in the analysis. We argue that young people blogging about serious illness demonstrate the inherent intercommunicative potential of blogging. We also argue that youth blogging about serious illness may represent a fruitful strategy for ill young people to create meaning, stay front-stage in youth communities and build self-esteem and confidence out of chaos. Furthermore, we argue that these blogs may contribute rather unique experience-based knowledge and reflections about existential issues to other young blog readers, who may otherwise not get access to this aspect of life. Youth blogging about serious illness thereby reflects a patient group so far not very visible and through the genre youth stand out as more competent when it comes to illness and healthcare issues than what is often presumed.